Growth rate and body size differences in Rangifer, a study of causes and effects - Reimers, Eigil (Rangifer, 1983)
The paper discusses growth rate- and body size differences in Rangifer; their causes and effects. Growth rates and autumn body weights vary considerably both within and between Rangifer subspecies. The variation measured is within limits found in animals of same genetical stock subjected to different environments. Reproductive age, pregnancy rate, calving time and mortality either are or may be functionally related to autumn body weights. The differences in growth rates and body size among Rangifer in different areas are caused primarily by differences in environmental factors during the summer, including stress. The quality of the winter pastures has a minor effect on the body size in areas where the summer conditions allow the animals to grow at their maximum rate. In areas where maximum growth rates for various reasons are counteracted, severely overgrazed winter pastures will contribute to reduced body size. Stress in the terms of human disturbance, insects and predators and the effect on Rangifer activity pattern and hence on growth rates and body size need to be more thoroughly dealt with. Forskjeller i vekst og størrelse hos Rangifer, en studie over årsaker og virkninger. Abstract in Norwegian / Sammendrag: Arbeidet diskuterer årsaker til og virkninger av vekst- og størrelsesforskjeller hos Rangifer. Vekst og høstvekter varierer betydelig både innen og mellom de enkelte Æangj/er-underartene. Variasjonene er imidlertid ikke større enn de som er beskrevet i bestander med samme genetiske utgangspunkt og utsatt for ulike miljøforhold. Alder ved kjønnsmodning, drektighetsfrekvens, kalvingstid og dødelighet er eller synes å være relatert til høstvektene. Vekst-og størrelsesforskjeller hos rein og caribou i ulike områder skyldes i første rekke forskjeller i miljøfaktorene om sommeren, stress inkludert. Kvaliteten av vinterbeitene har liten effekt på kroppsstørrelse i områder hvor forholdene sommerstid tillater maksimal veksthastighet. I områder hvor dette av forskjellige grunner ikke skjer, vil sterkt overbeitede vinterbeiter bidra til reduserte kroppsvekter. Stress i form av menneskelige forstyrrelser, insekter og rovdyr og effekten på reinens/caribouens aktivitetsbudsjett og derigjennom på vekst og kroppsvekt har krav på større forskningsinteresse. Rangiferin kasvun ja suuruuden eroavaisuuksia. Tutkielma syistå ja vaikutuksista. Abstract in Finnish / Yhteenveto: Tyo kåsittelee syitå ja vaikutuksia Rangiferin kasvu - ja suuruuseroavaisuuksista. Kasvu ja syyspainot vaihtelevat huomattavasti sekå yksittåisisså Rangifer - alalajeissa ettå lajien kesken. Vaihtelu ei ole kuitenkaan suurempi kuin se mitå on kerrottu laumoista, joilla on sama perinnollinen låhtokohta ja jotka ovat joutuneet erilaisten ymparistotekijoiden vaikuttamiksi. Sukukypsyysikå, tiinehtyvyystaajuus, vasonta-aika ja kuolleisuus on tai nåyttåå olevan suhteessa syyspainoihin. Syy kasvu - ja suuruuseroavaisuuksiin poroilla ja karibulla eri seuduilla nåyttåå ensi sijassa olevan ympåristotekijoiden eroavaisuudet kesållå, stressi mukaanluettuna. Talvilaitumien laadulla on pieni vaikutus ruumiin suuruuteen seuduilla, joissa olosuhteet kesåaikaan sallivat enimmåiskasvunopeuden. Seuduilla, joissa tåta ei tapahdu - eri syistå johtuen, voimakkaasti ylirasitetut talvilaitumet vaikuttavat alentuneisiin ruumiinpainoihin. Stressi, inhimillisten håirioden muodossa, hyonteiset ja petoelåimet ja poron/karibun vaikutus toimintaan sekå siten kasvuun ja ruumiinpainoon ovat seikkoja, jotka vaativat suurempaa tutkimuskiinnostusta.